OVERVIEW OF SERVICE ADMINISTRATION CONDITIONS BPJS OUTCOME PATIENTS AT X JOMBANG HOSPITAL - Indah Susilowati; Bela Maulidiah Ishak; Ninda Mulya Ike Ardilla; Nurhadi (Jurnal Kesehatan Mahardika, 2022)
The administrative requirements for registration of outpatients specifically for BPJS users, must be brought in full when visiting a hospital for a health check. The problem is from the number of 8 patients who visited the hospital including 2 patients who did not bring a control letter, 2 patients did not bring a photocopy of their ID card, 3 patients did not bring a photocopy of BPJS, and 1 patient came who had not been scheduled for control. The purpose of this study was to determine the suitability of the administrative requirements for outpatient registration of BPJS users at Hospital X Jombang. Descriptive research method with a cross sectional approach, the variables are policy regulations, standard operating procedures, administrative completeness of patient registration. The population of BPJS outpatients is 26,654, the sample is 30 by quota sampling and 1 respondent is the Head of Medical Records. As a result, policies and standard operating procedures have been implemented, administrative compliance is not complete, such as a control letter (20%), photocopy of ID card (56.7%), and photocopy of BPJS (53.3%). The conclusion is that the implementation of the outpatient registration procedure for BPJS users at Hospital X Jombang is not in accordance with the rules, because the patient administration requirements are not complete. This can cause the waiting time for the destination poly to be longer and hamper the service process at the patient registration area and cancel BPJS claims at the hospital. Suggestions for making information facilities related to completeness for outpatient registration requirements.